Biofilm formation and slime producing ability in Staphylococci causing subclinic bovine mastitis in the Zulia state-Venezuela - Kutchynskaya Valero-Leal; Jhoandry Rivera-Salazar; Wilfido Briñez; América Paz; Eyilde Piña; Yeiny Ávila; Gladis Colina López (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2017)
A total of 79 S. aureus strains and 47 coagulase negative Staphylococcus (CNS) isolates from cow milk suffering subclinical mastitis were investigated for their ability to form biofilm as one      of the most important virulence factors. Using Congo Red Agar method, 80% of S. aureus strains were slime producers, while in CNS was 32%. By microtiter plate method, 55%, 17%, and 28% of S. aureus isolates were strong, moderate, and weak biofilm producers, respectively, while in CNS the percentages were 43%, 17%, and 40%, respectively. All isolates were screened by Polymerase chain reaction (PCR) for amplification of intercellular adhesion gene A (icaA). In S. aureus isolates the icaA gene was present in 65 % while in CNS was 11%. The majority of S. aureus characterized in this study formed biofilm, which suggests that biofilm formation has an important role in the virulence of S. aureus isolated from bovine intramammary infections in Zulia state.